Problemy polskiej polityki innowacyjnej - Kozioł, Katarzyna (Problems of Polish Innovation Policy, 2009)
Analyzing the innovation policy of Poland since middle nineties, one can notice that a lack of decisive actions was one of the main factors of inappropriate innovation activity in the state. Programmes concerning the policy had clear objectives but there were no effective instruments to implement them.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 172-180